2017
DOI: 10.31258/jnat.16.2.47-53
|View full text |Cite
|
Sign up to set email alerts
|

Polimorfisme Penanda RAPD untuk Analisis Keragaman Genetik Pinusmerkusii di Hutan PendidikanUnhas

Abstract: PENDAHULUAN Pinus (Pinusmerkusii) merupakan tumbuhanGymnospermae atau berbiji terbuka yang memiliki tajuk pohon berbentuk cemaraatau kerucut dan daun berbentuk jarum. Pinus termasuk jenis yang cepat tumbuh dan dapat tumbuh baik pada tanah yang kurang subur serta tidak memerlukan tempat tumbuh dengan persyaratan khusus.Hampir semua bagian pohon dapat dimanfaatkan, antara lain bagian batangnya dapat disadap untuk diambil ABSTRACTThe aims of Genetic study of pinus identified stand in Unhas Experimental Forest is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 0 publications
1
3
0
4
Order By: Relevance
“…Thus, each RAPD marker probably detects a different location of DNA fragments in the genome of each kemiri sunan accession. This is in accordance with the research conducted by Gusmiaty et al (2016) who reported that each RAPD primer has its own annealing site on genomic DNA, therefore the polymorphic DNA bands generated from each primer differ in terms of band size and the number of DNA bands.…”
Section: Polymorphism Of Rapd Markers On Kemiri Sunan Accessionssupporting
confidence: 92%
“…Thus, each RAPD marker probably detects a different location of DNA fragments in the genome of each kemiri sunan accession. This is in accordance with the research conducted by Gusmiaty et al (2016) who reported that each RAPD primer has its own annealing site on genomic DNA, therefore the polymorphic DNA bands generated from each primer differ in terms of band size and the number of DNA bands.…”
Section: Polymorphism Of Rapd Markers On Kemiri Sunan Accessionssupporting
confidence: 92%
“…Polymorphism refers to the visualization of amplification based on different observed DNA fragments and score in order to determine whether the variation is presented by observing the sequence differences. RAPD is still used to analyze genetic diversity because of its ability to amplify various species, like Pinus merkusii [19] in Educational Forest Hasanuddin University, onion (Allium cepa L) [20], Dioscorea sp [21], and Indonesian Edible Canna (Canna indica L.) [22]. The comparison co-dominant and dominant primers have been performed in molecular research, in genetic diversity using RAPD and SSR of Ustilago hordei [23], and Zingiber officinale [24].…”
Section: Resultsmentioning
confidence: 99%
“…The kinship relationship between clones can be seen from the coefficient of similarity. The higher the similarity coefficient value, the closer the kinship between individuals and the closer the kinship, the lower the genetic distance [33]. Based on these criteria, it can be said that the clone Cin 25 and the clone Cin 18 have a fairly close relationship with the clone SKM 91.…”
Section: Diversity Of Agronomic Characteristicsmentioning
confidence: 99%